2019
DOI: 10.1007/s40093-019-0286-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of agro industrial wastes compost on soil health and onion yields improvements: study at field condition

Abstract: Purpose Industries are generating numerous amount and types of organic wastes to the environment. The aim of the present study was to investigate the effects of agro industrial wastes compost on soil physicochemical quality, soil microbial population, growth and yield of onion (Allium cepa L.) under field condition . Methods The experiment was conducted in a completely randomized plot design at field condition. Allium cepa L. was grown using five different levels of agro industrial wastes compost, three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Due to the multiple positive effects of integrated organic and chemical fertilizers on physical, chemical, and biological soil properties as shown in Tables 2-4, such integrated treatments contribute to the stabilization of and increase in final crop yields. Such treatments have the potential to improve different soil water relations, and replenish SOM and essential micronutrients, which ultimately lead to ameliorated soil health and offering higher crop yields [90,93]. The Pearson s correlation coefficient matrix between the grain yield of the two crops and different soil properties reaffirmed this finding, and it was found that the grain yield of two crops showed highly positive significant correlations with the different tested soil properties (r = 0.68-0.94), with the exception of soil pH that showed negative significant correlations with the grain yield of the different crops (r ranged from −0.64 to −0.70) (Figure 1).…”
Section: Impacts Of Inm Treatments On Grain Yield Of Different Cropsmentioning
confidence: 99%
“…Due to the multiple positive effects of integrated organic and chemical fertilizers on physical, chemical, and biological soil properties as shown in Tables 2-4, such integrated treatments contribute to the stabilization of and increase in final crop yields. Such treatments have the potential to improve different soil water relations, and replenish SOM and essential micronutrients, which ultimately lead to ameliorated soil health and offering higher crop yields [90,93]. The Pearson s correlation coefficient matrix between the grain yield of the two crops and different soil properties reaffirmed this finding, and it was found that the grain yield of two crops showed highly positive significant correlations with the different tested soil properties (r = 0.68-0.94), with the exception of soil pH that showed negative significant correlations with the grain yield of the different crops (r ranged from −0.64 to −0.70) (Figure 1).…”
Section: Impacts Of Inm Treatments On Grain Yield Of Different Cropsmentioning
confidence: 99%
“…Lou et al [41] reported that the application of mature composts derived from spent mushroom substrate increased the nitrogen content in the soil from 157.35 mg N kg −1 to 400 mg N kg −1 after 42 days of incubation as compared to the control. On the other hand, compost application also increased exchangeable sodium, potassium, calcium, magnesium, iron and copper as well as improved onion shoot numbers, shoot girth and shoot length [42].…”
Section: Sugarcane Bagassementioning
confidence: 96%
“…Lee, et al [14] also reported a slight increase in soil pH (7.31 to 7.81) due to treatment of food waste compost at application rates of 10 to 60 Mg/ha compared with control (7.16). Increment insoil pH after compost application was due to decomplexation of metal cations and mineralization of organic N [6] causing release of K + , Ca 2+ , Mg 2+ and OHduring the degradation of organic products in soil [15].…”
Section: Change In Physicochemical Propertiesmentioning
confidence: 99%